Health information systems architectures and strategies - Winter, Alfred 1959-; Haux, R. (Reinhold).; SpringerLink (Online service). (London New York Springer, 2011)
This book is a definitive introductory resource that tackles the pivotal role of information systems in health care. Illustrating the importance of information systems in delivering high-quality health care at the lowest possible cost, this book provides the essential resources needed by the health informatics / medical informatics specialist to understand and successfully manage the complex nature of hospital and transinstitutional health information systems. The book refines concepts described in the Editors' previous book Strategic Information Management in Hospitals and considers both the progress in the field and also the lessons learned. Perception of information systems in health care has changed. There is no longer a focus only on single institutions like hospitals, but health care institutions within health care networks come to the fore. In producing this new book, the Editors have broadened the focus from hospital information systems and their strategic management to strategic management of transinstitutional health information systems.
Health institutions and information processing -- Information system basics -- Health information systems -- Modeling health information systems -- Architecture of hospital information systems -- Specific aspects for architectures of transinstitutional health information systems -- Quality of health information systems -- Strategic information management in hospitals -- Strategic information management in health care networks.
Rev. ed. of: Strategic information management in hospitals / Reinhold Haux. c2004.
Electronic reproduction.
Keywords: Medical informatics; Information storage and retrieval systems -- Medical care; Medical records -- Data processing; Medical Informatics Applications; Computer Systems; Electronic books